Using Computer-Assisted Instruction to Increase Otolaryngology Education During Medical School - Margaret C. Michel; Arielle Thal; Andrew D. Sparks; Philip E. Zapanta (Association of American Medical Colleges, 2021)
Introduction A quarter of all complaints seen in adult primary care and half of all complaints seen in pediatric primary care are otolaryngology related. Even though half of all medical students enter primary care fields, there is no standardized curriculum for otolaryngology during medical school. Due to increasing limitations on specialty teaching during general medical education, computer-assisted instruction has been suggested as a format for increasing exposure to otolaryngology. Methods We designed a computer-based learning module for teaching high-yield otolaryngology topics for third- and fourth-year medical students during their primary care clerkship at our institution from 2016-2018. We evaluated students' prior otolaryngology knowledge with 11 case-based, multiple-choice questions and then evaluated the efficacy of the module by a similar posttest. Results Three-hundred and sixty-five students completed the module. The average pre- and posttest scores were 44% (SD = 21%) and 70% (SD = 17%), respectively, showing that the module resulted in significantly increased scores (p < .01). Discussion The improvement of test scores indicates that this module was an effective educational intervention at our institution for increasing exposure and improving otolaryngology knowledge in third- and fourth-year medical students. As medical schools shift toward adult learning principles such as independent and self-directed learning, computer-assisted instruction is an alternative to classroom-based didactics. Creating resources for independent study will allow more time for otolaryngology faculty and residents to teach clinical exam skills and interactive case-based discussions, which are less suitable to teach via computer-assisted instruction.